Faktor Pengaruh Tekanan Darah dan Fungsi Ginjal terhadap Lama Rawat Inap Pasien Kanker Ginjal Post Nefrektomi - Haikal Shiddiq; Exsa Hadibrata; Indri Windarti (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Kidney cancer is the third most common urological cancer, following prostate and bladder cancer, with renal cell carcinoma (RCC) being the most prevalent type, particularly in Europe and North America. Its incidence increases by approximately 0.5% each year as age advances, peaking between 60 and 70 years, and it is more frequently diagnosed in men at a ratio of 1.5:1. This study aims to analyze the impact of blood pressure and kidney function on the length of hospital stay for patients post-nephrectomy at RSUD H. Abdul Moeloek, Bandar Lampung, using a descriptive analytical method and a cross-sectional design with the entire population as the sample. The findings indicate a significant relationship between blood pressure and kidney function with the duration of hospitalization, where patients with high blood pressure are 6.41 times more likely to experience prolonged stays (p = 0.04), while those with elevated creatinine levels are 8 times more likely (p = 0.041). In conclusion, hypertension and decreased kidney function significantly contribute to the extension of hospital stays for patients after nephrectomy.